Migrantes Nordestinos na Região Metropolitana de São Paulo: características socioeconômicas e distribuição espacial - Maria das Neves Medeiros de Melo; Wilson Fusco (Confins)
The migration of the population born in the Northeast to the Southeast Region of Brazil, as the result of intense and historical regional inequalities, is one of the most important elements of Brazilian demographic dynamics. The volume of migrants, which grew each year, began to stabilize in the late 1970s, and the return migration, which was more important since the 1980s, gives new shades to the national scene. Particularly concentrated in the Metropolitan Region of São Paulo, a portion of the population born in the Northeast remained in the region of destination, despite the difficulties imposed by the selectivity of the labor market and the real estate market. Regarding this population, this study sought to identify socio-spatial characteristics that can be understood as result of the adaptation process to the changes observed in the destination region. For that, variables from the Demographic Censuses of 2000 and 2010 were used.